AIDA-Based Marketing Communication Strategy in Increasing Visitor Interest at Sei Mencirim Educational Tourism - Muhammad Aidil Azhar; Yusra Dewi Siregar (Ali Institute of Research and Publication, 2026)
This study aims to describe the AIDA-based marketing communication strategy implemented at Sei Mencirim Educational Tourism in increasing visitor interest. This research is motivated by the growing competition among educational tourism destinations and the need for destination managers to communicate attraction values through relevant promotional channels. This study used a descriptive qualitative approach. Data were collected through in-depth interviews with the owner, manager, and visitors, supported by field observation and documentation. The data were analyzed through data condensation, data display, and conclusion drawing. The findings indicate that the attention stage is built through visual promotion on social media, banners, brochures, and community-based information sharing. The interest stage is supported by educational activities, culinary variety, and family-oriented tourism experiences. The desire stage emerges from visitors’ positive impressions of the atmosphere, service, price suitability, and testimonials from previous visitors. Meanwhile, the action stage is reflected in visitors’ decisions to visit, purchase culinary products, and consider repeat visits. The study concludes that the AIDA model helps explain how marketing communication practices at Sei Mencirim Educational Tourism gradually shape visitor interest. However, the findings are limited to qualitative data, so further studies may include visitor statistics or social media engagement data.